Teoría de las prácticas sociales - Castro, Pedro V.; Gili Suriñach, Sylvia; Lull, Vicente; Chapman, Robert W.; Micó Pérez, Rafael; Rihuete Herrada, Cristina; Risch, Roberto; Sanahuja y Ii, M. Encarna (Complutum, 1996)
Sin resumen